The impact of exercise on self-esteem, anxiety, and depression on first-year students at the University of Venda - Tshikovhele, Khodani Lucky (My University, 2022)
Students who transition from school to tertiary institutions can experience stressors which lead to anxiety and depression. This can be alleviated by exercise. Limited research has been undertaken about exercise and the alleviation of depression amongst tertiary education students in South Africa. The aim of the study was to investigate the impact of exercise on depression, anxiety, and self-esteem on first-year students registered at the University of Venda (UNIVEN). A quantitative approach using a cross-sectional survey design was used. The study sample consisted of 320 randomly selected first-year students, 160 students who exercised regularly and 160 students who did not exercise at all. Data was collected using the Rosenberg Self-Esteem Scale (RSE), The Becks Anxiety Inventory (BAI), and the Becks Depression Inventory-11 (BDI-11). The study was theoretically underpinned by the trans theoretical model (TTM). Data analysis used both non-inferential and inferential statics that is, descriptive statistics, multivariate analysis of variance (MANOVA) and logistic regression analysis. The findings supported those found in previous research, both locally and internationally. The hypotheses of this study were fully supported by the results. Results pertaining to age and gender in this study revealed that there were no significant differences in scores. Additionally, respondents that had higher levels of anxiety, due to not exercising, were linked to pre-contemplation in the TTM. It was determined that these respondents were not aware of exercise as an intervention to enhance their overall well-being and mental health. Generally, the research contributes to understandings of the impact of exercise as an intervention in mental health challenges in first year tertiary education students. The exercise guidelines developed out of this research will help the Department of Education (DoE), UNIVEN and tertiary institutions generally in providing exercise interventions to undergraduate students in the tertiary education sector
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2022
Keywords: Exercise; Self-esteem; Depression; Anxiety; Self-esteem; Exercise -- Psychological aspects; Exercise therapy; Depression, Mental; Psychology students; College students -- South Africa -- Limpopo